Kepemimpinan dan Kerja Sama untuk Meraih Mutu Pendidikan: (Re-aktualisasi Peran Sumber Daya Manusia melalui Total Quality Management dalam Manajemen Pendidikan Islam) - Musayyidi Musayyidi; Hafid; Matlani (Kariman: Jurnal Pendidikan Keislaman, 2024)
There are four basic efforts that must be made in a product/service producing institution to produc  better quality, in this case an islamic  educational institution, namely : (1) Creating a “win win” situation  an not “win win” situation. “lose win” between parties  with an interest  in product / service  producing  institutions  (stakehoulders). In this case, especially between  the leadhership / owner of the institution and the staff  of the institution, there must  be mutually  beneficial  conditions  for each  other in achieving  thue quality  of the products / service produced by the institutions (2) it is necessary  to develop instrinsic motivation in everyone involved in the process  of achieving product / service  quality. Every person  must grow  motivated  that the result  of their activites reach  a certain  quality that  continues to improve, especially  in accordance  with the needs and expectations of user / subcribbes. (3) every leader must be oriented towards  long-term process and results. Impelementing TQM is not a short-term change process, but a consistent  and continous  log-term  effort (4) in mobilizing  all institutional  capabilities  to achieve the specified  quality, cooperation must  be developed be results.  There should  be no competion between  them that interferes with the process of achieving quality results  they are a unit that must work together and cannot  be separated from each other to produce quality products / services as expected.